Dietary enrichment with Highly Unsaturated Fatty Acid (HUFA) during rearing phase of Nereis virens: growth performance, fatty and amino acid - VIVI ENDAR HERAWATI; SETO WINDARTO; M. ARFAN (Society for Indonesian Biodiversity, 2023)
Abstract. Herawati VE, Windarto S, Arfan M. 2023. Dietary enrichment with Highly Unsaturated Fatty Acid (HUFA) during the rearing phase of marine worms (Nereis virens) in growth performance, fatty acid profiles, and amino acid profiles. Biodiversitas 24: 3828-3834. Nereis virens is a species of marine worm that belongs to Polychaeta. Nereis virens is often utilized as a natural feed for shrimp broodstock related to its main content of fatty acids to accelerate gonad maturity. The enrichment of Highly Unsaturated Fatty Acid (HUFA) is thought to stimulate diet protein and support growth, survival, and nutritional content. This study aimed to discover and examine the growth performance, amino acid profile, and fatty acid profile of N. virens in the rearing stage with a HUFA-enriched diet. The research was conducted from May to September 2022 at MSTP (Marine Science Techno Park ) Jepara. The experimental animals used were 45 marine worms per rearing container, weighing 14-16g/container. The research method is experimental, with a completely randomized design (CRD) of 4 treatments and 3 replicates. The treatments in this study consisted of a commercial diet without the HUFA (A), with the enrichment of 0.50 ml HUFA (B), 1 ml HUFA (C), and 1.50 ml HUFA (D). The results showed that diets with the enrichment with HUFA had a significant effect (P<0.05) on Absolute Growth (Ag); Relative Growth Rate (RGR); Efficiency of Feed Utilization (EFU), Protein Efficiency Ratio (PER) and no significant effect (P>0.05) on SR. The highest RGR, EFU, PER, and SR values were in the treatment with the enrichment with 1.50 ml HUFA (D) with the following values of 5.77 ± 0.20g/day, 85.20 ± 2.75g, 2.05 ± 0.08%, and 100 ± 0.00%. Nutritional quality based on proximate protein and fatty acid fat results were highest in the enrichment treatment with 1.50 ml HUFA (D), 53.80% protein and 19.67% fat. The highest amino acid and fatty acid profiles in the same treatment were 41.15 ppm and 6.60% EPA.